Role of Facebook in Influencing Customer Purchase Intention in Nepalgunj, Nepal (Victoria Journal of Management, 2025)
This study examines the role of Facebook in influencing customer purchase intention in the context of Nepalgunj. In today’s complex world of technology, social media has evolved as the new and effective way of marketing a product. With the usage of internet, specially social media has changed the way of operating businesses. To survive and excel in the competitive environment, businesses has to adopt the social media marketing techniques to promote its products. To achieve the objective of the study, a close ended structured questionnaire with five scale Likert scale is prepared and data are collected through online survey with sample size of 216. The study uses SPSS, the Pearson correlation model is used to examine the relationship of attention and interest, trustworthiness, celebrity endorsement, product information and review, Facebook community/group and customer purchase intention. The focus of the research is on the purchase intentions of customer influenced by Facebook. The construct is at the pre purchase and leads the motivational aspects that affect customer behavior. The finding of this study indicates that of attention and interest, trustworthiness, product information and review, Facebook community/group, have a significant role on customer purchase intention in Nepalgunj, Banke, Nepal while celebrity endorsement does not affect on customer purchase intention.